"Inspiring poetic heritage in the poetry of Ibn al-Khatib of Andalusia." - barkat.amin, barkat.amin (El Omda in Linguistics and Discourse Analysis, 2018)
Summary : The main purpose of this study; is to examine the manifestation of the poet heritage in the texts of Ibn-Khatib-Alanalusi through inernal reading of his diffarant poetry, accordinig to the extensive reading of artistic reding.This study amis also to benfit from the approaches that are relly capable of rising the poeťs oum vision of the poetic heritage and the disclosure of the imitatipn and overrid areas of the poetic in buiding his texts